Literature Reflection on Financial Statement Consolidation from the Perspective of the Statement of Financial Accounting Standards (PSAK) - Dionisius Andika Wisnu Pradana; Siti Nur Aini; Elvira Fitri Nuraini; Endang Kartini Panggiarti (Escalate : Economics and Business Journal, 2025)
This article aims to analyze and compare consolidated financial statements from year to year based on the provisions and guidelines stipulated in the Statement of Financial Accounting Standards (PSAK). Using a literature review approach, this study highlights changes in presentation, disclosure, and the impact of the implementation of the latest PSAK on the consistency and transparency of an entity's financial statements. The implementation of PSAK has brought significant progress to the quality of consolidated financial statements in Indonesia. However, improvements in practice are still needed, particularly in harmonization between PSAKs, improving internal control, and uniformity of disclosure to make financial statements more relevant and transparent.